Single‐incision laparoscopic surgery for rectal cancer: early results and medium‐term oncological outcome. (December 2015) - Gash, K.; Bicsak, M.; Dixon, A.
Abstract: Aim: Conventional laparoscopic surgery for rectal cancer management is now widely accepted as an alternative to open surgery, bestowing specific advantages without causing detriment to oncological outcome. Evolving from this, single‐incision laparoscopic surgery (SILS) has been successfully utilized for the removal of colonic tumours, but the literature lacks data analysing the suitability of SILS for rectal cancer resection, particularly on oncological outcome. We report the medium‐term oncological outcome from a prospective observational study of SILS for rectal cancer, including high and low anterior resections. Method: A prospective electronic database was collated of all patients undergoing SILS rectal cancer resection in our institution, between 2009 and 2014. In addition to patient, tumour and operative data, histopathological and medium‐term oncological end‐points were recorded. Kaplan–Meier curves were used to analyse survival. Results: Sixty‐one patients underwent SILS for rectal cancer by high anterior resection ( n = 34), low anterior resection with total mesorectal excision (TME) ( n = 24) and low anterior resection with TME and hand‐sewn colo‐anal anastomosis ( n = 3). The median operation time was 105 (37–280) min and 92% of cases were completed by SILS. The mean interval to resuming oral feeding was 11 h and the median length of stay was 2 (1–8) days. The median number of lymph nodes found by the histopathologist in the resected specimen was 18 (6–44) and all operations completely removed the tumour (R0 resection). At a median follow‐up of 46 (16–64) months, eight (13%) patients developed metastatic disease, of whom three had local recurrence. Overall, three patients have died, of whom all had metastatic disease. Conclusion: Anterior resection with TME for rectal cancer can be safely performed using the SILS technique, with acceptable histopathological results and good oncological outcome.